DIVERSITY OF GENRES IN UZBEK FOLKLORE ART (E Global Congress, 2025)
This article examines one of the ancient and deeply rooted genres of the Uzbek national musical heritage—folklore art—and its performance traditions. The study highlights the significant role of folklore within Uzbek oral creativity, exploring how its diverse genres have been shaped, transmitted, and preserved across generations. Particular attention is given to the historical sources that document the evolution of Uzbek folklore forms, as well as the cultural functions they have fulfilled in various social contexts. The article also reflects on the artistic, ritual, and communicative features of traditional genres such as yalla, olan, lapar, terma, and aytim, demonstrating their contribution to the broader cultural identity of the Uzbek people.